The effect of viscoelasticity and damage in relation to the acceleration of fatigue and creep testing of composites using time-temperature superposition - Xu, Fei (2018)
This project is focused on accelerating fatigue tests and constant strain rate (CSR) creep tests for composites which are widely used in aircraft due to a higher strength-to-weight ratio. To achieve this ultimate objective, research will be conducted to establish a damage model for linear viscoelastic materials and combine this model with time temperature superposition principle (TTSP). Since the mechanical behaviour of polymer resins exhibits linear viscoelastic properties which are time and temperature dependent, we wish to accelerate fatigue test by using the TTSP which is empirical and phenomenological. Then a damage model needs to be built for these linear viscoelastic materials to provide a physically-based interpretation for TTSP. To understand the properties of viscoelastic materials, a complete damage model was constructed for linear viscoelastic UD composites. Firstly, the damage representation for the corresponding elastic UD composites with an array of dispersed matrix cracks was derived from Li’s work based on continuum damage mechanics (CDM). The elastic-viscoelastic correspondence principle was used to obtain the damage representation for corresponding linear viscoelastic UD composites in the Laplace domain. Secondly, a damage evolution law for the transverse direction of the UD composites was derived by making using of the Weibull distribution of defects, and by assuming that damage is driven by strain. To explain the time and temperature effects on the strength of the UD composites, a long-term creep strength prediction model was built by taking advantage of conventional strength prediction models, known as the global load sharing (GLS) model and simultaneous fibre failure (SFF) model. Finally, a rational test acceleration method was proposed by modelling the behaviour of the UD composites during deformation.